Biologija celice: Navodila za laboratorijske vaje - Dariš, Barbara; Lipovšek, Saška (University of Maribor Press, 2021)
Cell Biology: Laboratory Work. Laboratory work is divided in 13 chapters. All major topics in the field of cell biology for medicine students are presented. 7. 5. 2025 Fourth reprint of the second edition. 31. 5. 2023 Third reprint of the second edition.